Fintech and inclusive growth: Evidence from 25 Asian developing countries - Md. Al-Amin Parvez; Evanta Hashem Katha; Mashrura Kabir Shaeba; Md. Sajjad Hossain (Asian Development Bank Institute (ADBI), 2023)
The primary objective of this study is to unveil the impact of FinTech through financial development, financial inclusion, and institutional quality on the inclusive growth of 25 developing countries in Asia. To serve this purpose, the Human Development Index (HDI), the dependent variable, has been taken as the proxy for inclusive growth along with a set of independent variables in a well-balanced panel data set, which is then analyzed to see the impact of changing levels of independent variables on human development for the period 2014-2021. The results show that increasing the level of FinTech along with the Findex, financial inclusion, and institutional quality may increase human development.
Keywords: C23; D31; D63; F02; 330; FinTech; financial inclusion; inequality; panel data model; Hausman test